BMI trajectories and risk factors among 2-11-year-old children by their immigrant status: evidence from the Longitudinal Study of Australian Children. Issue 7 (9th July 2019) - Zulfiqar, Tehzeeb; Burns, Richard A; D'Este, Catherine; Strazdins, Lyndall
Abstract : Objective: This study aimed to identify body mass index (BMI) trajectories and their predictors in Australian children by their maternal immigrant status. Methods: Data on 4142 children aged 2–3 years were drawn from the birth cohort of the Longitudinal Study of Australian Children. BMI was calculated according to the International Obesity Task Force cut-off points. Immigrant status was determined by the Australian Bureau of Statistics and the United Nations Development Programme, Human Development Index criteria. Latent class growth analysis estimated distinct BMI trajectories, and multinomial logistic regression analysis examined factors associated with these BMI trajectories. Results: Two BMI groups and six BMI trajectories were identified. The stable trajectories group included high-risk (10%, n=375), moderate-risk (5%, n=215) and low-risk (68%, n=2861) BMI trajectories. The changing trajectories group included delayed-risk (6%, n=234), gradual-risk (8%, n=314) and declining-risk (3%, n=143) BMI trajectories. We found some evidence that children of immigrants from low-and middle-income countries were more likely to have moderate-risk and high-risk BMI trajectories compared with low-risk BMI trajectory. However, these associations were insignificant in fully adjusted models. The explanatory risk factors for moderate-risk and high-risk BMI trajectory were birth weight, family socioeconomic position, and organised sports participation. Our results also suggest that 4–7 years of age may be important for the prevention of overweight/obesity in children. Discussion: A better understanding of the risk factors associated with distinct BMI trajectories in immigrant children will inform effective preventive strategies. Some of these risk factors such as non-participation in organised sports, and high screen time, may also impede the integration of immigrant children into the host culture. Obesity prevention strategies aimed at increasing physical activities in immigrant children could help deliver a social and health benefit by increasing social integration among children of immigrants and Australians.